2007
DOI: 10.1159/000112209
|View full text |Cite
|
Sign up to set email alerts
|

Lower Erythrocyte Glutathione Peroxidase Activity in Bronchopulmonary Dysplasia in the First Week of Neonatal Life

Abstract: Background: Bronchopulmonary dysplasia (BPD) is a major pulmonary complication in premature infants and is considered a free radical disorder. Erythrocyte catalase (CAT) and cellular glutathione peroxidase (c-GPx) are antioxidant enzymes that detoxify peroxides generated from dismutation of superoxide anion. The study goal was to measure enzyme activity for preterm infants during the first week of life. Methods: Blood samples were collected from umbilical arterial lines or the radial artery of 44 preterm infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In adult rat lungs, Audi et al [75] demonstrated that prolonged exposition to hyperoxia could increase lung NQO1 activity giving rise to higher duroquinone reduction along its pass through the pulmonary circulation. By analyzing blood samples of premature newborn taken from umbilical or radial artery, Fu et al [76] showed that low c-GPx activity in perinatal life could increase susceptibility to BPD since they observed that preterm newborns affected by BPD show lower cellular Gpx activity compared with the ones that do not develop BPD. Cho et al [77] studied the role and molecular events mediated through the Nrf2 pathway all along the late phase of lung maturation by using transriptomic analysis in models of neonatal Nrf2 −/− and Nrf2 +/+ mice exposed to hyperoxia.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samementioning
confidence: 99%
“…In adult rat lungs, Audi et al [75] demonstrated that prolonged exposition to hyperoxia could increase lung NQO1 activity giving rise to higher duroquinone reduction along its pass through the pulmonary circulation. By analyzing blood samples of premature newborn taken from umbilical or radial artery, Fu et al [76] showed that low c-GPx activity in perinatal life could increase susceptibility to BPD since they observed that preterm newborns affected by BPD show lower cellular Gpx activity compared with the ones that do not develop BPD. Cho et al [77] studied the role and molecular events mediated through the Nrf2 pathway all along the late phase of lung maturation by using transriptomic analysis in models of neonatal Nrf2 −/− and Nrf2 +/+ mice exposed to hyperoxia.…”
Section: Nrf2 and Heme Oxygenase-1 (Ho-1) Main Characters Of The Samementioning
confidence: 99%
“…The low GPX activity is probably unable to protect from oxidative injury and may contribute to the degree of respiratory distress. Many other authors also drew the same conclusion, showing the preponderant protective role of the glutathione-cycle enzymes, espe cially GPX, which is postulated to be an etiolo gic factor in chronic lung disease in preterm infants (38)(39)(40)(41). The activity of the first (SOD) and second (GPX) step of antioxidant enzymes must therefore be ba lanced to prevent oxidative damage in cells.…”
Section: Discussionmentioning
confidence: 81%
“…Antioxidant enzymes continue to be studied in neonates. A recent report indicated that erythrocyte cellular glutathione peroxidase may play an important role in the development of BPD, with lower levels of activity present in early postnatal life being a potential risk factor for BPD [29]. Due to antioxidant deficiencies in preterm infants, numerous studies have been performed to assess the potential benefits of antioxidant therapy.…”
Section: Postnatal Factors In Bpdmentioning
confidence: 99%